Interplay between Transcription Factors and the Epigenome: Insight from the Role of RUNX1 in Leukemia - Brettingham-Moore, Kate H.; Taberlay, Phillippa C.; Holloway, Adele F. (Frontiers in Immunology, 2015)
The genome has the ability to respond in a precise and co-ordinated manner to cellular signals. It achieves this through the concerted actions of transcription factors and the chromatin platform, which are targets of the signalling pathways. Our understanding of the molecular mechanisms through which transcription factors and the chromatin landscape each control gene activity has expanded dramatically over recent years, and attention has now turned to understanding the complex, multifaceted interplay between these regulatory layers in normal and disease states. It has become apparent that transcription factors as well as the components and modifiers of the epigenetic machinery are frequent targets of genomic alterations in cancer cells. Through the study of these factors, we can gain unique insight into the dynamic interplay between transcription factors and the epigenome, and how their dysregulation leads to aberrant gene expression programs in cancer. Here we will highlight how these factors normally co-operate to establish and maintain the transcriptional and epigenetic landscape of cells, and how this is reprogrammed in cancer, focusing on the RUNX1 transcription factor and oncogenic derivative RUNX1-ETO in leukemia as paradigms of transcriptional and epigenetic reprogramming.